2015
DOI: 10.1002/pmic.201500070
|View full text |Cite
|
Sign up to set email alerts
|

Expression of proteins in superior and inferior spikelets of rice during grain filling under different irrigation regimes

Abstract: Poor grain filling of later-flowering inferior spikelets is a serious problem in modern rice cultivars, but the reason and regulation remain unclear. This study investigated post-anthesis protein expression in relation with grain filling and the possibility to use irrigation methods to enhance grain filling through regulating protein expression. One japonica rice cultivar was field-grown under three irrigation treatments imposed during the grain filling period: alternate wetting and moderate soil-drying (WMD),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 73 publications
3
17
0
Order By: Relevance
“…Such findings suggested that those biological processes including protein and major CHO metabolism as well as photosynthesis are likely to be negatively affected during rice grain-filling in IS, while the processes of development and stress responses are highly correlated with the poor graining of IS. More interestingly, in this study, the number of proteins with reduced abundances is 3–4 times more than the number of proteins with increased abundances, similar to a previous gel-based proteomics investigation comparing the grain-filling process between IS and SS (Chen et al, 2016). In addition, we analyzed the identified proteins from SWATH-MS data using a multifaceted bioinformatic approach for the comprehensive elaboration of differentially expressed proteins between IS and SS.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…Such findings suggested that those biological processes including protein and major CHO metabolism as well as photosynthesis are likely to be negatively affected during rice grain-filling in IS, while the processes of development and stress responses are highly correlated with the poor graining of IS. More interestingly, in this study, the number of proteins with reduced abundances is 3–4 times more than the number of proteins with increased abundances, similar to a previous gel-based proteomics investigation comparing the grain-filling process between IS and SS (Chen et al, 2016). In addition, we analyzed the identified proteins from SWATH-MS data using a multifaceted bioinformatic approach for the comprehensive elaboration of differentially expressed proteins between IS and SS.…”
Section: Resultssupporting
confidence: 88%
“…The overall down-regulation of photosynthesis-related proteins in IS possibly led to an unfavorable environment that in turn affected the activity of enzymes involved in glycolysis and sucrose-to-starch conversion, thus contributing to the poor graining of IS. Moreover, abundances of proteins involved in the photosynthetic photorespiration (Os03g57220 and Os12g22030) and Calvin cycle (e.g., Os03g03720 and Os01g02880) were also shown to be decreased in IS compared to SS, consistent with the photosynthetic proteome changes occurring in previous investigation of proteome changes between IS and SS (Zhang et al, 2014; Chen et al, 2016). However, the number of photosynthesis-related proteins identified in this study were three–fourfold more in comparison to the proteomics data of previous 2D gel-based studies between IS and SS (Zhang et al, 2014, 2015), indicating a high throughput and accuracy advantage of SWATH-based technology used in this study and also enrich the understanding of photosynthesis proteins involve the grain-filling process.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations